Transporters Buffer Synaptically Released Glutamate on a Submillisecond Time Scale - Diamond, Jeffrey S. (J Neurosci, 1997)
The role of transporters in clearing free glutamate from the synaptic cleft was studied in rat CA1 hippocampal neurons cultured on glial microislands. The time course of free glutamate in the cleft during a synaptic event was estimated by measuring the extent to which the rapidly dissociating AMPA receptor antagonist kynurenate (KYN) was replaced by glutamate during a synaptic response. Dose inhibition of the AMPA receptor EPSC by KYN was less than predicted by the equilibrium affinity of the antagonist, and the rise time of AMPA receptor miniature EPSCs (mEPSCs) was slowed by KYN. Both results indicated that KYN dissociated from AMPA receptors and was replaced by synaptically released transmitter. When transporters were blocked byd,l-threo-β-hydroxyaspartic acid (THA) or Li(+), the mEPSC rise time in the presence of KYN was slowed further, indicating that transporters affect the glutamate concentration in the first few hundred microseconds of the synaptic response. The glutamate transient necessary to cause these effects was determined by developing a detailed kinetic model of the AMPA receptor. The model replicated the effects of KYN on the amplitude and rise time of the synaptic responses when driven by glutamate transients that were similar to previous estimates (Clements et al., 1992; Clements, 1996). The effects of THA were replicated by slowing and enlarging the slower phase of the dual component transient by about 20% or by prolonging the single component by almost 40%. Because transport is too slow to account for these effects, it is concluded that transporters buffer glutamate in the synaptic cleft.